Physiological characteristics of an aging Olympic athlete - Nybo, L.; Schmidt, J. F.; Fritzdorf, S.; Nordsborg, N. B. (Medicine & Science in Sports & Exercise, 2014)
Purpose: To investigate the physiological basis of continued world-class performance of a world-class rower who won medals (three gold and two bronze) at five consecutive Olympic Games.